Prediction of Febrile Seizures in Febrile Children with Upper Respiratory Infection - Elif Çelik; Şükrü Güngör; Müge Ayanoğlu; Ayşe Tosun (Galenos Yayinevi, 2023)
Introduction:Febrile seizures (FS) are the most frequently encountered childhood neurological problems. They cause stress and anxiety for parents and a considerable workload for healthcare providers. The purpose of this study was to identify useful markers capable of predicting the risk of FS in febrile children with upper respiratory infection using complete blood count parameters.Methods:Four hundred seventy-six children aged between 6 months and 5 years, 240 with a history of first FS, 121 with acute febrile upper respiratory tract infection without seizures (AFI), and 115 healthy controls were included in the study. Two age-and sex-matched control groups were recruited, one consisting of febrile patients without seizures and the other of healthy children.Results:Logistic regression analysis of all participants together revealed that a hemoglobin (Hb) level ≤10.95 was associated with a 2.937 -fold greater risk of FS, and a neutrophil to lymphocyte ratio (NLR) ≥1.3969 with a 2.719-fold increase in FS (95% confidence interval: 1.885-4.576 vs. 1.873-3.949), (p<0.001).Conclusion:Although low Hb levels and high NLR can be used to predict the risk of FS, these values alone are not sufficient to predict FS in children with AFI.